Atmospheric deposition and exceedances of critical loads from 1800−2025 for the conterminous United States. Issue 4 (1st May 2018) - Clark, Christopher M.; Phelan, Jennifer; Doraiswamy, Prakash; Buckley, John; Cajka, James C.; Dennis, Robin L.; Lynch, Jason; Nolte, Christopher G.; Spero, Tanya L.
Abstract: Atmospheric deposition of nitrogen (N) and sulfur (S) has increased dramatically over pre‐industrial levels, with many potential impacts on terrestrial and aquatic ecosystems. Quantitative thresholds, termed "critical loads" (CLs), have been developed to estimate the deposition rate above which damage is thought to occur. However, there remains no comprehensive comparison of when, where, and over what time periods individual CLs have been exceeded. We addressed this knowledge gap by combining several published data sources for historical and contemporary deposition, and overlaying these on six CL types from the National Critical Loads Database (NCLDv2.5; terrestrial acidification, aquatic acidification, lichen, nitrate leaching, plant community composition, and forest‐tree health) to examine exceedances from 1800 to 2011. We expressed CLs as the minimum, 10th, and 50th percentiles within 12‐km grid cells. Minimum CLs were relatively uniform across the country (200–400 eq·ha −1 ·yr −1 ), and have been exceeded for decades beginning in the early 20th century. The area exceeding minimum CLs peaked in the 1970s and 1980s, exposing 300, 000 to 3 million km 2 (depending on the CL type) to harmful levels of deposition, with a total area exceeded of 5.8 million km 2 ( 70% of the conterminous United States). Since then, deposition levels have dropped, especially for S, with modest reductions in exceedance by 2011 for all CL types, totaling 5.2 million km 2 in exceedance. The 10th and 50th percentile CLs followed similar trends, but were not consistently available at the 12‐km grid scale. We also examined near‐term future deposition and exceedances in 2025 under current air quality regulations, and under various scenarios of climate change and additional nitrogen management controls. Current regulations were projected to reduce exceedances of any CL from 5.2 million km 2 in 2011 to 4.8 million km 2 in 2025. None of the additional N management or climate scenarios significantly affected areal exceedances, although exceedance severity declined. In total, it is clear that many CLs have been exceeded for decades, and are likely to remain so in the short term under current policies. Additionally, we suggest many areas for improvement to enhance our understanding of deposition and its effects to support informed decision making.